Self-employment in Wales during the COVID-19 pandemic - Andrew Henley; Darja Reuschke; Elizabeth Daniel; Victoria Price (Welsh Economic Review (WER), 2021)
The economic fall-out from the COVID-19 crisis continues to wreak serious damage in the labour market, and at the time of writing the full extent of this damage is some way from becoming apparent. One significant group of workers who have been very badly affected by the economic shock resulting from 'lockdown' are the self-employed. In previous analysis it was reported that almost 4 in 10 of the jobs created in Wales over the decade following the 2008 financial crisis were in self-employment (Henley and Lang, 2017). Furthermore, this analysis demonstrated the high degree of diversity of self-employment activity across Wales, both in spatial and sectoral dimensions. This paper looks at how this group in Wales have fared so far during the crisis and makes some suggestions on how policy may address the prospects of the self-employed.
Keywords: 330; Coronavirus; Selbstständige; Wales